Age as a Mortality Predictor in ECPR Patients - Spacek, Radim; Weiss, Vojtech; Kavalkova, Petra; Jiravsky, Otakar; Barcak, Jan; Belohlavek, Jan (Medicina (Kaunas, Lithuania), 2024)
Extracorporeal cardiopulmonary resuscitation (ECPR) is an advanced technique using extracorporeal membrane oxygenation (ECMO) to support patients with refractory cardiac arrest. Age significantly influences ECPR outcomes, with younger patients generally experiencing better survival and neurological outcomes due to many aspects. This review explores the impact of age on ECPR effectiveness, emphasizing the need to consider age alongside other clinical factors in patient selection. Survival rates differ notably between in-hospital (IHCA) and out-of-hospital cardiac arrest (OHCA), highlighting the importance of rapid intervention. The potential of artificial intelligence to develop predictive models for ECPR outcomes is discussed, aiming to improve decision-making. Ethical considerations around age-based treatment decisions are also addressed. This review advocates for a balanced approach to ECPR, integrating clinical and ethical perspectives to optimize patient outcomes across all age groups.
Keywords: Heart Arrest; extracorporeal; srdeční zástava; mimotělní membránová oxygenace; Cardiopulmonary Resuscitation; age; ECPR; ECMO; věkové faktory; kardiopulmonální resuscitace; resuscitation; Humans; Extracorporeal Membrane Oxygenation; cardiopulmonary; Out-of-Hospital Cardiac Arrest; Age Factors; outcomes; zástava srdce mimo nemocnici; lidé